2016
DOI: 10.3847/1538-4357/833/1/49
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Magnetic Fluctuations and Electron Non-Thermal Temperature Anisotropy: Survey of Wind-Swe-Veis Observations

Abstract: The solar wind electron velocity distribution function (eVDF) exhibits a variety of non-thermal features that deviate from thermal equilibrium. These deviations from equilibrium provide a local source for electromagnetic fluctuation emissions, including the commonly observed electron whistler-cyclotron and firehose instabilities. We present a systematic analysis of Wind-SWE-VEIS observations of solar wind electron plasma and associated Wind-MFI observed magnetic fluctuations. For the first time using the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…Another relevant factor is the free energy of the solar wind expanding along the interplanetary magnetic field, which is expected to accumulate in a temperature anisotropy of protons (ions) > T T , where Pand ⊥ denote directions relative to the magnetic field (Chew et al 1956). For electrons the situation is slightly different, although their temperature anisotropy shows the same tendency, i.e., > T T , with increasing the distance from the Sun, see Figure 8 in Štverák et al (2008; the average behavior of the temperature anisotropy can be found in Adrian et al 2016). However, the anisotropy reported by the observations at large enough heliocentric distances, e.g., 1 au, is much below these expectation (Adrian et al 2016;Chen et al 2016).…”
Section: Introductionmentioning
confidence: 79%
“…Another relevant factor is the free energy of the solar wind expanding along the interplanetary magnetic field, which is expected to accumulate in a temperature anisotropy of protons (ions) > T T , where Pand ⊥ denote directions relative to the magnetic field (Chew et al 1956). For electrons the situation is slightly different, although their temperature anisotropy shows the same tendency, i.e., > T T , with increasing the distance from the Sun, see Figure 8 in Štverák et al (2008; the average behavior of the temperature anisotropy can be found in Adrian et al 2016). However, the anisotropy reported by the observations at large enough heliocentric distances, e.g., 1 au, is much below these expectation (Adrian et al 2016;Chen et al 2016).…”
Section: Introductionmentioning
confidence: 79%
“…Several spacecraft observations in the Earth's magnetosheath [ Anderson et al ., ; Fuselier et al ., ; Phan et al ., ; Tan et al ., ; Gary et al ., ; Xu and Chen , ] and in the solar wind [ Marsch , ; Marsch et al ., , , ; Gary et al ., , ; Kasper et al , ; Hellinger et al ., ; Matteini et al ., , ; Bale et al ., ; Maruca et al ., ; Bourouaine et al ., ; Stverak et al ., ; Adrian et al ., ] show that the inverse correlations between temperature anisotropy and parallel beta exist pervasively. In addition, various numerical analysis and computer simulations for homogeneous space plasma have been conducted in order to confirm the above theoretical phenomenon over the last two decades [ Devine and Chapman , ; Gary et al ., , ; Gary and Nishimura , ; Yoon and Seough , ; Seough and Yoon , ].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetosheath temperature anisotropy instability problem was first extended to the solar wind proper and solar corona, by Gary et al (2001a, b). Many subsequent works followed including those by , Kasper et al (2003Kasper et al ( , 2008, Marsch et al (2004Marsch et al ( , 2006, , , Matteini et al (2007Matteini et al ( , 2012, Bale et al (2009), Bourouaine et al (2010, Maruca et al (2011Maruca et al ( , 2012, Osman et al (2011Osman et al ( , 2012Osman et al ( , 2013, Marsch (2012), , Adrian et al (2016), and others that the present review might have missed. These works further investigated the effects of temperature anisotropy instabilities in the solar wind by analyzing data obtained from an armada of spacecraft including Helios, Ulysses, WIND, ACE, Stereo, etc.…”
Section: Introductionmentioning
confidence: 99%